Implementasi Metode Bin-Nazhar dalam Program Ekstrakurikuler Tahfidz Munjiat di Madrasah Aliyah - Qori'ah, St. Fatihatul; Hasan, Nor (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to examine the implementation of the Bin-Nazhar Method in the Tahfidz Munjiat extracurricular program at MA Al-Khadijah, Pamekasan. The Bin-Nazhar Method is an approach to memorizing the Quran through repeated readings while still consulting the Mushaf. The study used a qualitative approach with a case study. Data collection techniques included participant observation, in-depth interviews with the supervising teacher (Ustad Hermawan), and documentation studies. The results indicate that the implementation of this method proceeded systematically through three main stages: (1) preparation by determining a memorization target of at least 5 verses, (2) the core process of repeating the readings (muroja'ah) until fluent, and (3) evaluation through memorization (tasmi') accompanied by a repetition of previous verses. The main supporting factors include students' religious commitment, institutional support through the habit of Dhuha prayer, and the active role of the supervising teacher. Meanwhile, inhibiting factors were time constraints due to busy academic schedules and differences in absorption and concentration among students. This study concludes that the Bin-Nazhar Method is effective in building strong and structured memorization of the Munjiat Surahs, with its success highly dependent on discipline in the muroja'ah process and consistency in tasmi'.